Tan Malaka, gerakan kiri, dan revolusi Indonesia - Poeze, Harry A. (KITLV-Jakarta Yayasan Obor Indonesia, 2008)
History of revolution in Indonesia, 1945-1949 and involvement of Tan Malaka in fighting against the Dutch.